IMPACT OF PANDEMIC SITUATION ON MICRO LEVEL ENTREPRENEUR OF DELHI - Surjan, Praveen Kumar; Bhan, Suraj (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research paper is about the effect of pandemic situation on the micro level entrepreneurs of Delhi. In this research paper, researcher also mapped the problem and difficulties such as social, economic as well as educational of micro level entrepreneurs faced during the pandemic situation. The pandemic situation influenced the production and income from a stop-over or even exit from the market; scaling-down output after a huge fall in demand; falling market demand and a increasing shortage of manpower; increasing expenses and decreasing revenues too. Most of the micro level entrepreneurs faced the challenges, issues and problems due to the lock-down. The unforeseen appearance of the pandemic situation imposed the interruption not only the micro levels entrepreneurs of Delhi even the entire world has been faced this crucial situation. For this research paper author executed the Structured questionnaire with the help of purposive representative sampling technique on 250 respondents. It was Survey research in nature. For the analysis of the obtained data, mixed method technique has been used in which statistical analysis techniques for quantitative analysis and Thematic formation technique for qualitative data analysis has used. The gathered data reveals that almost all the micro level entrepreneurs have been adversely affected and were facing different issues with a certain degree of loss, closing the business, very low Margin, heavy loss in the business, lack of supply of goods and marketing-related problems etc.